1994
DOI: 10.1016/s0140-6736(94)90818-4
|View full text |Cite
|
Sign up to set email alerts
|

p53 mutation hotspot in radon-associated lung cancer

Abstract: Mutations in gene p53 are the most common defects in lung cancer and may be a pathway through which environmental carcinogens initiate cancer. We investigated p53 mutations in lung cancers from uranium miners with high radon exposure. 16 (31%) of 52 large-cell and squamous-cell cancers from miners contained the same AGG to ATG transversion at codon 249, including cancers from 3 or 5 miners who had never smoked. This specific mutation has been reported in only 1 of 241 published p53 mutations from lung cancers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(51 citation statements)
references
References 4 publications
5
45
0
1
Order By: Relevance
“…In our cases with NK/T-cell lymphoma, exon 5 is the most common site for mutations, ie, 13 of 30 (43%) mutations occurred in exon 5. Some carcinogens might cause mutation in specific codons, as was observed in the mutation of codon 249 in lung and liver cancers induced by irradiation (Anderson et al, 1995;Taylor et al, 1994). Relatively restricted distribution of mutational spots were found in our cases; codon 273, one of the so-called mutational "hot spots" (Hollstein et al, 1991), was involved in 2 cases, and codons 151, 193, and 251 were involved in 2 or 3 cases.…”
Section: Et Alsupporting
confidence: 58%
“…In our cases with NK/T-cell lymphoma, exon 5 is the most common site for mutations, ie, 13 of 30 (43%) mutations occurred in exon 5. Some carcinogens might cause mutation in specific codons, as was observed in the mutation of codon 249 in lung and liver cancers induced by irradiation (Anderson et al, 1995;Taylor et al, 1994). Relatively restricted distribution of mutational spots were found in our cases; codon 273, one of the so-called mutational "hot spots" (Hollstein et al, 1991), was involved in 2 cases, and codons 151, 193, and 251 were involved in 2 or 3 cases.…”
Section: Et Alsupporting
confidence: 58%
“…At molecular level, exposure to radon and alpha particles may lead to hypoxanthineguanine phosphoribosyl transferase (hprt) gene mutations that ranged from complete deletion of the gene, partial deletions to gene rearrangements (Lutze et al 1992). Occupational studies on uranium miners also showed that about 31% of lung cancers contained the same mutation at codon 249 of the p53 gene (Vahakangas et al 1992;Taylor et al 1994). These genetic and cytogenetic changes attributed to radon have been reported to be linear and dose-dependent in many in vitro and in vivo experiments.…”
Section: Discussionmentioning
confidence: 97%
“…The occurrence of p53 mutations has even been associated with a shortened patient survival (Horio et al, 1994), although this finding could not be verified by other authors (Van Zandwijk et al, 1995). Certain p53 mutations appeared to be specific for radon-associated lung cancer (Taylor et al, 1994). The protein product of the p53 gene represents an important tumour suppressor protein that is also detectable in serum (Fontanini et al, 1994).…”
Section: Discussionmentioning
confidence: 97%